Evaluation and Treatment of Open Distal Humeral Fractures. Issue 1 (3rd January 2017) - Zimmer, Zachary R.; Horneff, John G.; Taylor, Ryan M.; Levin, L. Scott; Kovach, Stephen; Mehta, Samir
Abstract : The complex anatomy of the distal aspect of the humerus, in combination with the challenge of treating the traumatized soft-tissue envelope, addressing bone and articular cartilage loss, and minimizing postoperative complications, often leads to suboptimal outcomes following the treatment of open distal humeral fractures. The overall goals of treatment should focus on rigid fixation, maintaining or restoring a viable soft-tissue envelope, restoring functional range of motion, and limiting complications. Although uncommon, some open distal humeral fractures are associated with concomitant injuries and are associated with complex fracture patterns involving the entire articular surface. The initial treatment of an open distal humeral fracture includes tetanus prophylaxis and the administration of antibiotics followed by excisional debridement to reduce the risk of infection. Multiple operative fixation strategies have been used, including external fixation, internal fixation, and total elbow arthroplasty, each of which may be better suited for particular patients and fracture patterns. For large soft-tissue defects, the early use of soft-tissue procedures to provide adequate and stable wound coverage can result in improved outcomes and fewer complications.